Habitat and nest placement of Red-backed Shrikes Lanius collurio breeding in clear-cuts in southern Norway - Lislevand, Terje (Ornis Norvegica, 2012)
Information on habitat, nest placement, phenology and clutch size in Red-backed Shrikes Lanius collurio was collected from a total of 71 nests in southern Norway during 1995–2009. In this area, which is situated at the north-western limit of the species’ distribution, breeding was predictable in clear-cuts in pine Pinus sylvestris forest where junipers Juniperus communis made up a large part of the shrub layer. This contrasts with previous descriptions of typical shrike habitat in clear-cuts which focused on the availability of young spruce Picea abies trees. Nests were almost exclusively located in Junipers (92%), further emphasizing the importance of this bush species as part of the shrike habitat in the study area. Mean nest height was 113 cm (range 0–250 cm) and increased with height of the nesting bush (mean = 225, range 120–400 cm). However, this increase was lower than expected if the relationship was simply proportional, indicating that the birds prefer to place their nests low in the vegetation even if higher alternatives are available. Clutch size ranged from 1 to 7 eggs (mean = 5.1) and estimated dates of first eggs varied from 10 May to 16 June (median = 3 June). Breeding time varied significantly between years but there was no correlation between breeding time and clutch size. Both height of nest and height of the nest bush increased significantly with breeding season, and possible reasons for these findings are discussed.